Chlorella vulgaris cell disruption using copper sulfate. Issue 8 (14th September 2021) - Garoma, Temesgen; Yazdi, Ramin E.; Chin, Cintia; Jain, Anurag
Abstract: This study evaluated the feasibility of using copper sulfate as an agent for Chlorella vulgaris cell disruption. About 70% of the cells in a C. vulgaris suspension at ∼0.2 g/L concentration were disrupted at a copper sulfate dose of 500 mg/L as Cu and 72-hour contact time. Scanning electron microscope morphology of C. vulgaris cells confirmed that the cells were ruptured after treatment with copper sulfate. The effect of rupturing increased the lipid extraction yield. For a 10% C. vulgaris paste dosed with copper sulfate at 200 mg as Cu/g of dry algae and 24-hour contact time, the lipid extraction yield increased by 30% with respect to control samples. The specific energy requirement and CO2 emissions per kg of dry algae were estimated as 2.82 MJ and 0.26 kg CO2 -eq., respectively. The existing algal cell disruption methods have estimated energy requirements of 10 to 300 times and CO2 emissions of 20 to 600 times greater than those of copper sulfate. Despite these advantages, the adaption of copper sulfate as an algal cell disruption method may be limited by the 24-hour contact time needed to achieve a significant increase in lipid extraction yield. Therefore, it is recommended that future research efforts be focused on addressing this challenge.